2007
DOI: 10.3317/jraas.2007.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of ACE genotype and predominantly diastolic hypertension: a preliminary study

Abstract: Paper AbstractBackground. The insertion/deletion (I/D) angiotensin-converting enzyme (ACE) polymorphism has been established as a cardiovascular risk factor in some populations, but the association with essential hypertension is controversial. Predominantly diastolic hypertension (PDH), or narrow pulse pressure hypertension, has been shown to have increased peripheral resistance. Because a DD genotype has been associated with higher plasma ACE levels and angiotensin II activity, we genotyped PDH patients for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
5
19
0
Order By: Relevance
“…Our results are concordant with those of Jiménez et al [64] who reported on the association between the DD genotype and predominantly diastolic hypertension. Increased blood pressure in homozygous subjects for the D allele could contribute to a more severe clinical course and a steeper development of end-stage renal disease.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are concordant with those of Jiménez et al [64] who reported on the association between the DD genotype and predominantly diastolic hypertension. Increased blood pressure in homozygous subjects for the D allele could contribute to a more severe clinical course and a steeper development of end-stage renal disease.…”
Section: Discussionsupporting
confidence: 94%
“…Some explain this inconsistency with genetic and environmental heterogeneity between different ethnic groups (Bautista et al 2004;Zhang et al 2007;Higaki et al 2000;Jiménez et al 2007;Companioni Nápoles et al 2007) as well as ACE I/D polymorphism gene's complex interaction with other genetic factors that contribute to the expression of HT (Nawaz and Hasnain 2008).…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, it is assumed that the reninangiotensin-aldosterone system is part of a pathway implicated in the pathogenesis of different pregnancy complications. 4 In particular, the intron 16 insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE), which critically influences plasma ACE activity 5,6 and angiotensin peptide levels, 7 and which is implicated in the pathogenesis of different diseases, 8,9 is discussed as a possible genetic risk factor for pre-eclampsia. 10,11 Moreover, there are a few studies indicating a possible influence of the ACE I/D genotype on risk of foetal loss (FL) under certain circumstances.…”
Section: Introductionmentioning
confidence: 99%